2019
DOI: 10.1113/jp277321
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting human cerebral blood flow responses to augmented blood pressure oscillations

Abstract: Key points Cerebral autoregulation is most effective in buffering against pressure fluctuations slower than 0.03 Hz (∼30 s). This suggests that frequency bands for characterizing cerebral autoregulation should be redefined Low cross‐spectral coherence below 0.03 Hz highlights the limitations of transfer function approaches Haemodynamic changes induced by lower body pressure could not fully explain the differences in autoregulation estimated from spontaneous vs. augmented fluctuations, and thus, observations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…We have previously shown that the coherence at the frequency bands used in this study is a relatively reliable measure of the integrity of autoregulation, although the gain and phase shift may be less reliable [29]. By definition, effective autoregulation should be a low coherence state, which in turn, creates uncertainties around the estimated gain and phase relation [31,32].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have previously shown that the coherence at the frequency bands used in this study is a relatively reliable measure of the integrity of autoregulation, although the gain and phase shift may be less reliable [29]. By definition, effective autoregulation should be a low coherence state, which in turn, creates uncertainties around the estimated gain and phase relation [31,32].…”
Section: Discussionmentioning
confidence: 84%
“…Third, we used conventional frequency ranges to assess cerebral autoregulation. However, as noted before [ 27 , 28 ], these were chosen to standardize the assessment of autoregulation across studies, and in reality, autoregulation is most effective at frequencies at or lower than 0.03 Hz [ 29 ]. Fourth, cerebral autoregulation may be affected by multiple variables that were not adequately assessed in our study, such as medications [ 41 ], pre-morbid vascular risk factors, and critical illness, including sepsis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, neurogenic (sympathetic and parasympathetic) components cause vasoconstriction in counteracting a rise in arterial pressure. In addition, cerebral autoregulation has been reported to be effective for a slower change in blood pressure (> 30 s), whereas it is less so during faster changes [16,17]. Based on the previous findings, the changes in cerebral blood flow in this study may be explained as follows: the fastest parasympathetic and the subsequent sympathetic reflexes counteracted the fast increase in blood pressure, thus resulting in vasoconstriction that was reflected in the decreased oxy-and deoxy-hemoglobin signals of the NIRS.…”
Section: Discussionmentioning
confidence: 99%
“…This was to elicit fluctuations in bloodthus, perfusionpressure sufficiently large enough to engage cerebral autoregulatory mechanisms. 19,29,30 Autoregulation was determined by deriving the relationship between mean arterial pressure (independent variable; input variable) and MCAv (dependent variable; output variable) fluctuations using a validated nonlinear and nonparametric approach based on projection pursuit regression (PPR). 31 This approach has been validated and shown to have excellent reproducibility (Lin's concordance coefficient >0.95 across repeat-assessments).…”
Section: Cerebral Autoregulationmentioning
confidence: 99%